UPAYA DETEKSI DINI SINDROM METABOLIK BERBASIS KELUARGA MELALUI PEMBERDAYAAN KADER KESEHATAN - N Nuryani; Marselia Sandalayuk; Herman Hatta (P3M Universitas Aisyiyah Surakarta, 2022)
The incidence of non communicable disease (NCD) such as heart disease, diabetes mellitus, stroke, chronic kidney desease, and obesity in Gorontalo tends to be increase, which is above the national prevalence. The predisposition of NCD generally identified from the incidence of metabolic syndrome which is characterized by obesity, increased triglycerides and blood glucose, low high density lipoprotein (HDL) and hypertension. Metabolic syndrom can increase the incidence of morbidity and mortality due to vascular disease. Early detection the risk of metabolic syndrome can be done through empowering health cadres in carrying out a family based approach in the community. So that the progression of metabolic syndrome can be prevent towards NCD disease. The aim of training health cadres is (1) increasing the role of health cadres in improving health status (2) increasing the abilities and skills of health cadres in identifying risk factors for metabolic syndrome. Implementation of activities in the form of delivering material with lecture methods, interactive discussions and direct practice. The media used in this training was power points, modules and a few materials to support the practice of measuring blood pressure, nutritional status base on body mass index, blood glucose and cholesterol profile. Evaluation of activities using a questionnaire before and after training. The results was indicated an increase in the knowledge and skills of health cadres after attending the training.